Information on the Impact National N-Power Scheme on Employment Creation - Frank M. Attah; Thomas A. Omang; Mary U. Ojong-Ejoh; Hussein Botchway (JINAV: Journal of Information and Visualization, 2021)
This study attempts to provide valuable data on the impact of the National N-Power scheme on youth employment in Bekwara Local Government Area of Cross River state. The ex post facto research design was adopted in collecting data from 398 samples from a population of 632 beneficiaries of the scheme using a self-structured questionnaire. The convenience sampling technique was used in selecting the samples from the study area. Data collected from the field was analyzed using inferential and descriptive statistics. The descriptive statistics include frequency distribution, charts, simple per centages, means and standard deviation. The result from the descriptive statistics was then subjected to parametric statistics at 0.05 confidence level. Out of the 398-instrument distributed, only 389 was returned and used for analysis. from the analysis, it was discovered that nearly all the respondents (96.92%) were unemployed before becoming beneficiaries of the N-Power Scheme. It was also discovered that out of all the programs registered under the scheme, only three programs had beneficiaries in Bekwara, these were N-Teach, N-Agro and N-Health. From the analysis carried out using lineal regression, it was discovered that there is a significant relationship between N-Power and Employment Creation. Based on these findings the study recommends amongst others that there is a need for an increase in the number of beneficiaries of the Scheme in the Local Government Area.